[Au12(SR)6]2−, As Smaller 8‐Electron Gold Nanocluster Retaining an SP3‐Core. Evaluation of Bonding and Optical Properties from Relativistic DFT Calculations. Issue 15 (6th June 2018) - Muñoz‐Castro, Alvaro; Saillard, Jean‐Yves
Abstract: Exploring the versatility of atomically precise clusters is a relevant issue in the design of functional nanostructures. Superatomic clusters offer an ideal framework to gain further understanding of the different distinctive size‐dependent physical and chemical properties. Here, we propose [Au12 (SR)6 ] 2− as a minimal 8‐electron superatom related to the prototypical [Au25 (SR)18 ] − cluster, depicting half of its core‐mass (2.3 kDa vs 5.0 kDa). The [Au12 (SMe)6 ] 2− cluster fulfills a 1S 2 1P 6 electronic configuration, with a distorted tetrahedral Au8 core further viewed as an SP 3 ‐hybridized superatom. The distinctive optical properties show a blue‐shift for the first relevant 1P→1D transition, in comparison to [Au25 (SR)18 ] − . In addition, chiroptical activity is observed, denoting intrinsic core chirality. We expect that our results can shed light into the variation of the molecular properties according to the size‐dependent properties, and serve as guidelines for further experimental exploration of minimal or ultrasmall nanoclusters. Abstract : The versatility of atomic precision : superatomic clusters offer ideal frameworks to gain understanding of different distinctive size‐dependent physical and chemical properties. [Au12 (SR)] 2− is explored as a minimal 8‐electron superatom. The cluster fulfils a 1S 2 1P 6 electronic configuration, with a distorted tetrahedral Au8 core. The optical properties and chiroptical activities are compared to the prototypical [Au25 (SR)18 ] −‐ cluster.